Customer Loyalty to Scarlett: The Role of Quality, Trust, Discount, Price and Brand Image - Sherly Tandy; Yolanda Soedibyo (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to determine the effect of quality, trust, discount, price and brand image on customer loyalty through customer satisfaction on Scarlett product consumers. The data used are responses from questionnaires that have been distributed via googleform with sample data of 180 responses. In this study, data processing was carried out using SPSS using the regression equation. Meanwhile, the research scale used is measurement with the Likert Scale, which is the simplest method of measuring attitudes using a scale distribution to see the development or change in attitudes of respondents. The test results obtained in this study are that the variables trust, discount and price have an effect on customer satisfaction, while the variables quality and brand image do not have a direct effect on customer satisfaction. Then the influence of the variables quality, trust, discount and customer satisfaction has an effect on customer loyalty, while the variables price and brand image have no direct effect on customer loyalty. The results of this study indicate that to achieve customer loyalty, Scarlett can start by increasing trust. Because Scarlett consumers consider trust to have an effect on customer satisfaction and customer loyalty.